Architecture and mosaics in recently discovered Palaeochristian basilicas - Şahin, Mustafa (2016)
The excavations of the Dericik Early Christian Basilicas revealed the importance of the surrounding area of Bursa for understanding Early Christianity between the Late Roman and Early Byzantine periods. In the salvage excavations of 2001, the basic plan of the basilica (nave, narthex, presbyterium and apse) was revealed. The most important artefacts uncovered in that year were the mosaic pavements with geometric and plant ornaments and a grave located in the North Eastern corner of the church. The mosaic of the basilica was laid with the opus tessellatum technique on a thick mortar foundation with white, red, yellow, olive green and dark blue tesserae. A refrigerium scene is represented in the middle of the narthex mosaic. The mosaic in the centre of the nave is divided into parts, one of which with figures of birds inside octagons. In the transitional area between the nave and apse, three heavily damaged inscriptions have been conserved each of three or four lines, one of them indicating the wish of Epituchanos, diakôn, a church member.